Computational Design of Photocured Polymers Using Stochastic Reaction–Diffusion Simulation (Adv. Theory Simul. 7/2018). Issue 7 (5th July 2018) - Sarkar, Swarnavo; Lin‐Gibson, Sheng
Abstract : Photopolymerization During polymerization, network growth, crosslinking, and fluctuation events occur as stochastic processes. In article number1800028, Swarnavo Sarkar and Sheng Lin‐Gibson present a method to simulate these processes as a function of reaction rates and network configuration. Hence, a computational map from polymerization rates to network heterogeneity and physical properties is obtained.